2022
DOI: 10.3390/molecules27030969
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Valorization Strategy of Wine Industry by-Products and Their Application in Cosmetics—Case Study: Grape Pomace and Grapeseed

Abstract: Grape pomace and grapeseed are agro-industrial by-products, whose inadequate treatment generates socioeconomic and environmental concerns. Nevertheless, it is possible to valorize them by extracting their bioactive compounds, such as antioxidants (phenolic compounds), vitamin E and fatty acids. The bioactive compounds were extracted using solid-liquid extraction. The yields for phenolic compounds were 18.4 ± 0.4% for grape pomace, and 17.4 ± 0.4%, for grapeseed. For the oil, the yields were 13.3 ± 0.2% and 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 70 publications
0
29
0
2
Order By: Relevance
“…No phase separation (i.e., coalescence or sedimentation) or color change, was observed after centrifuge and heat-shock treatments. Ferreira, S. M. et al also confirmed the stability of the creams containing polyphenols over 2 months, as no separation was detected after centrifugation or thermal stress [ 37 ]. From a rheological point of view, polyphenols were found to be stable when incorporated into commercial creams and would, therefore, serve as a great pioneer for the skincare industry.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…No phase separation (i.e., coalescence or sedimentation) or color change, was observed after centrifuge and heat-shock treatments. Ferreira, S. M. et al also confirmed the stability of the creams containing polyphenols over 2 months, as no separation was detected after centrifugation or thermal stress [ 37 ]. From a rheological point of view, polyphenols were found to be stable when incorporated into commercial creams and would, therefore, serve as a great pioneer for the skincare industry.…”
Section: Resultsmentioning
confidence: 96%
“…The use of toxic solvents was avoided, and glycerin was used instead of ethanol, since it is safer and also a skin emollient solvent, which prevents the skin from dryness [ 36 ]. Ferreira et al used ethanol as medium for the extraction of polyphenols, but this water-soluble solvent is also considered a more erosive compound when applied to the skin compared to glycerin, which is more eco-friendly as well [ 37 ]. The same extraction procedure was applied to the recovery of the main bioactive compounds from the five different varieties of grape seeds: Marselan, Syrah, Obeidi, Cabernet Franc, and Asswad Karech.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, consumers look for cosmetics mainly composed of natural ingredients and with fewer negative effects on the environment. Hereupon, researchers started to study the possibility of using the waste produced from food and plant processing to attain bioactive ingredients, mainly antioxidants, that prevent the oxidation of the product and help to reduce the oxidative damage of cellular components, and antimicrobial agents, ingredients that have antibacterial, antifungal, and antiviral properties [ 14 , 15 , 16 ]. This strategy has helped to develop greener and value-added cosmetics, as well as to reduce and recycle waste, diminishing their environmental, social, and economic impact.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large amount of the weight of processed grapes (20-30%) remains as waste, which represents about 10 to 20 thousand tons of residues per year. The inadequate disposal and treatment of these residues represent a waste management issue at socioeconomic and environmental levels, with the last one characterized by contributing to an increase in the emission of gases with the greenhouse effect (Silva et al 2020;Ferreira and Santos 2022). The Isabel grape is among the most used grape cultivars to produce juice, wine, jam, raisins and as a table grape, with emphasis on Brazil and the United States as the largest producers (Silva et al 2017;Kurt-Celebi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…products with high added value (Silva et al 2021). Considering the growing concern with sustainability and the circular economy model, the opportunities to reuse grape by-products should bring great socioeconomic and environmental benefits (Ferreira and Santos 2022).…”
Section: Introductionmentioning
confidence: 99%